Laparoscopic hysterectomy to manage uterine rupture due to placenta percreta in the first trimester: A case report - Fan Lee; Katelin Zahn; Andrea K. Knittel; Jessica Morse; Michelle Louie (Elsevier, 2020)
Placenta percreta causing uterine rupture is a rare complication of pregnancy. It is most commonly diagnosed after the second trimester and can lead to significant morbidity necessitating abdominal hysterectomy of a gravid or immediately postpartum uterus. We describe a patient who presented with abdominal pain at 13 weeks of gestation and was diagnosed with placenta percreta during laparoscopy for presumed appendicitis. Intraoperatively, placenta was seen perforating the uterine fundus and 1 l of hemoperitoneum was evacuated. However, the uterus was hemostatic and the patient was stable, so the procedure was terminated. The patient was then transferred to a tertiary care center, where she ultimately underwent an uncomplicated laparoscopic gravid hysterectomy. We conclude that placenta percreta can occur in the first trimester even in patients without traditional risk factors. In stable patients, it is appropriate to consider minimally invasive hysterectomy with utilization of specific techniques to minimize intraoperative blood loss. Keywords: Uterine rupture, Placenta percreta, First trimester, Laparoscopic hysterectomy